Effect of posaconazole on the concentration of intravenous and oral cyclosporine in patients undergoing hematopoietic stem cell transplantation - Li-E Zhu; Hui-Ping Huang; Yi-Peng Cai; Yan Wang; Bao-Hua Xu; Mao-Bai Liu; Xue-Mei Wu (European Journal of Clinical Pharmacology, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Assessing the joint effects of brain aging and gut microbiota on the risks of psychiatric disorders - Huijie Zhang; Li Liu; Shiqiang Cheng; Yumeng Jia; Yan Wen; Xuena Yang; Peilin Meng; Chun’e Li; Chuyu Pan; Yujing Chen; Zhen Zhang; Jingxi Zhang; et al. (Brain Imaging and Behavior, 2022)

Electrospun nanofibers food packaging: trends and applications in food systems - Dur E. Sameen; Saeed Ahmed; Rui Lu; Rui Li; Jianwu Dai; Wen Qin; Qing Zhang; Suqing Li; Yaowen Liu (Critical Reviews in Food Science and Nutrition, 2022)

Evidence of interactions between sharks and Indo‐Pacific humpback dolphins ( Sousa chinensis ) in the northern South China Sea - Agathe Serres; Wenzhi Lin; Eric E. G. Clua; Mingli Lin; Mingming Liu; Songhai Li (Marine Mammal Science, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

An adaptive data cleaning framework: a case study of the water quality monitoring system in China - Zeng Chen; Peng Jiang; Jun Liu; Song Zheng; Zhenyu Shan; Zhihua Li; Huan Xu; Igor V. Bychkov; Alexei E. Hmelnov (Hydrological Sciences Journal, 2022)

River Flood Susceptibility and Basin Maturity Analyzed Using a Coupled Approach of Geo-morphometric Parameters and SWAT Model - Shan-e-hyder Soomro; Caihong Hu; Muhammad Waseem Boota; Zubair Ahmed; Liu Chengshuai; Han Zhenyue; Li Xiang; Mairaj Hyder Alias Aamir Soomro (Water Resources Management, 2022)

Immunostimulatory effect of quaternary degree and acetyl group of quaternized chitosan on macrophages RAW 264.7 - Xiaomin Li; Rong’e Xing; Chaojie Xu; Song Liu; Yukun Qin; Kecheng Li; Huahua Yu; Pengcheng Li (Journal of Oceanology and Limnology, 2022)

Impact of land use on surface water quality: a case study of active agriculturally disturbed basin in China - L. Zhang; X. Liu; H. Wei; C. Yang; E. Li; Z. Wang (International Journal of Environmental Science and Technology, 2022)

Research progress on antimicrobial materials for food packaging - Saeed Ahmed; Dur E. Sameen; Rui Lu; Rui Li; Jianwu Dai; Wen Qin; Yaowen Liu (Critical Reviews in Food Science and Nutrition, 2022)

Sterols and triterpenoids from Ganoderma lucidum and their reversal activities of tumor multidrug resistance - Min Wu; Cui-e Shen; Qiao-fa Lin; Jin-yi Zhong; Yan-fei Zhou; Ben-chen Liu; Jian-hua Xu; Zhi-qiang Zhang; Peng Li (Natural Product Research, 2022)

Another Record: Ocean Warming Continues through 2021 despite La Niña Conditions - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Zhetao Tan; et al. (Advances in Atmospheric Sciences, 2022)
The increased concentration of greenhouse gases in the atmosphere from human activities traps heat within the climate system and increases ocean heat content (OHC). Here, we provide the first analysis of recent OHC changes through 2021 from two international groups. The world ocean, in 2021, was the hottest ever recorded by humans, and the 2021 annual OHC value is even higher than last year’s record value by 14 ± 11 ZJ (1 zetta J = 10 21 J) using the IAP/CAS dataset and by 16 ± 10 ZJ using NCEI/NOAA dataset. The long-term ocean warming is larger in the Atlantic and Southern Oceans than in other regions and is mainly attributed, via climate model simulations, to an increase in anthropogenic greenhouse gas concentrations. The year-to-year variation of OHC is primarily tied to the El Niño-Southern Oscillation (ENSO). In the seven maritime domains of the Indian, Tropical Atlantic, North Atlantic, Northwest Pacific, North Pacific, Southern oceans, and the Mediterranean Sea, robust warming is observed but with distinct inter-annual to decadal variability. Four out of seven domains showed record-high heat content in 2021. The anomalous global and regional ocean warming established in this study should be incorporated into climate risk assessments, adaptation, and mitigation.

Circular RNA screening identifies circMYLK4 as a regulator of fast/slow myofibers in porcine skeletal muscles - Haigang Cao; Jieming Liu; Tianning Du; Yihao Liu; Xiaoyu Zhang; Yuan Guo; Jie Wang; Xiaomin Zhou; Xiao Li; Gongshe Yang; Xin’e Shi (Molecular Genetics and Genomics, 2022)
The type of myofiber is related to the quality of meat. The slow oxidized myofiber helps to increase the tenderness and juiciness of muscle. Numerous studies have shown that circRNA plays a key role in skeletal muscle development. However, the role of circRNA in porcine skeletal myofiber types is unclear. In this study, we performed high-throughput RNA sequencing to study the differential expression of circRNA in the longissimus dorsi and the soleus muscle. A total of 40,757 circRNAs were identified, of which 181 were significantly different. Interestingly, some circRNAs were involved in metabolism pathways, AMPK, FoxO, and PI3K-Akt signaling pathways. Besides, we focused on a novel circRNA-circMYLK4. By injecting circMYLK4-AAV into piglets, we found that circMYLK4 significantly increased the mRNA and protein levels of the slow muscle marker genes. In summary, our study laid an essential foundation for further research of circRNA in myofiber type conversion and higher meat quality.

Integer ambiguity resolution and precise positioning for tight integration of BDS-3, GPS, GALILEO, and QZSS overlapping frequencies signals - Guang’e Chen; Bofeng Li; Zhiteng Zhang; Tianxia Liu (GPS Solutions, 2022)